Analysis of Residual Free Chlorine Content in Rinjani Waterpark Swimming Pool Water, East Lombok District - Wahyudin, Wahyudin; Fatmalia, Enida; Yuliansari, Dini (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Water is the most essential component in daily life. One of its uses is as water in swimming pools. A swimming pool is a public place and facility in the form of a pool building used for swimming. The water used in swimming pools must have a quality that complies with the quality standards determined for the water. One of the parameters required in PERMENKES Nomor 2 Tahun 2023 is the remaining free chlorine. This research aims to analyze the residual free chlorine content in Rinjani Waterpark swimming pool water, where it is known from the results of preliminary studies that Rinjani Waterpark uses chlorine as a disinfectant to kill bacteria in the water and purify the pool water. There were several complaints from swimming pool visitors, such as eye irritation and itchy skin after swimming in that swimming pool, so further analysis was needed. The type of research used in this research is descriptive qualitative. The samples used in this research were 4 samples. The sampling technique uses total sampling. Testing was carried out at the STTL Mataram laboratory to see the free chlorine content in water samples using Mohr's Argentometry method. After conducting the research, the results were obtained that the samples that did not meet the requirements were samples with codes P1 M=2.3 mg/L, P3 M=1.77 mg/L, P4 M=2.3 mg/L, and P3 A = 0 mg/L. Visitors who want to visit the Rinjani Waterpark swimming pool are expected to use personal protective equipment (PPE) such as swimming goggles to avoid the impact of chlorine levels that are too high in the water. Swimming pool managers should pay attention to the chlorine dosage in the water so that it does not cause side effects to visitors.